Politics on display yard signs and the politicization of social spaces - Makse, Todd; Minkoff, Scott L.; Sokhey, Anand Edward 1981- (Oxford University Press, 2019)
Political yard signs are one of the most ubiquitous and conspicuous features of American political campaigns, yet they have received relatively little attention as a form of political communication or participation. In Politics on Display, Todd Makse, Scott L. Minkoff, and Anand E. Sokhey tackle this phenomenon to craft a larger argument about the politics of identity and space in contemporary America. Documenting political life in two suburban communities and a major metropolitan area, they use an unprecedented research design that leverages street-level observation of the placement of yard signs and neighborhood-specific survey research that delves into the attitudes, behavior, and social networks of residents. The authors then integrate these data into a geo-database that also includes demographic and election data. Supplemented by nationally-representative data sources, the book brings together insights from political communication, political psychology, and political geography. Against a backdrop of conflict and division, this book advances a new understanding of how citizens experience campaigns, why many still insist on airing their views in public, and what happens when social spaces become political spaces.-- Back cover.